2011
DOI: 10.1111/j.1463-1326.2011.01443.x
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of human islet α‐ and β‐cells

Abstract: Pancreatic islet cell regeneration is considered to be important in the onset and progression of diabetes and as a potential cell therapy. Current hypotheses, largely based on rodent studies, indicate continuous turnover and plasticity of α-and β-cells in adults; cell populations in rodents respond to increased secretory demand in obesity (30-fold β-cell increase) and pregnancy. Turnover and plasticity of islet cells decrease in mice within >1 year. In man, morphometric observations on postmortem pancreas have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 62 publications
5
63
0
1
Order By: Relevance
“…To answer this question, we used both mouse and human islets, as these differ in several aspects, such as cytoarchitecture, cellular plasticity, and turnover (18)(19)(20). Mouse islets were isolated from young mature (2 mo) and old (18 mo) virgin male C57BL/6 mice Significance The regulation of blood glucose is a homeostatic process that declines with age, but it is unknown whether this disturbance is a consequence of intrinsic dysfunction of the regulatory organ, the pancreatic islet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To answer this question, we used both mouse and human islets, as these differ in several aspects, such as cytoarchitecture, cellular plasticity, and turnover (18)(19)(20). Mouse islets were isolated from young mature (2 mo) and old (18 mo) virgin male C57BL/6 mice Significance The regulation of blood glucose is a homeostatic process that declines with age, but it is unknown whether this disturbance is a consequence of intrinsic dysfunction of the regulatory organ, the pancreatic islet.…”
Section: Resultsmentioning
confidence: 99%
“…To answer this question, we used both mouse and human islets, as these differ in several aspects, such as cytoarchitecture, cellular plasticity, and turnover (18)(19)(20). Mouse islets were isolated from young mature (2 mo) and old (18 mo) virgin male C57BL/6 mice…”
Section: Resultsmentioning
confidence: 99%
“…Intermediate cells expressing both β-and α-cell markers were observed in the regenerative areas supported the evidence for α-to β-cell transdifferentiation [26]. While β-cell replication is the best supported mechanism to account for islet regeneration in rodents, human β-cells only possess a limited capacity to replicate, and in both human and rodents the capacity declines with age [28]. This could suggest that neogenesis might be the most common mechanism to drive endogenous formation of β-cells in the human pancreas, and observations of single cells and small insulin positive clusters found near the ducts in human pancreas is suggestive for progenitor cells residing in 2 Alloxan treatment selectively destroys insulin-producing cells in the pancreas when administered to rodents and thereby induce pancreatic regeneration [29][30][31][32][33][34].…”
Section: Transdifferentiation Of α-Cells To β-Cellsmentioning
confidence: 74%
“…Cnop et al measured the lipofuscin content of islet cells and reported that the number of islet cells in humans is largely established by age 20 years and then remains constant with a low turnover rate (Cnop et al 2010(Cnop et al , 2011. More recently, Mizukami et al reported that Ki67-a marker for cell proliferation-positive rate of β and non-β islet cells is prominent in childhood but significantly decreased over 20 years of age (Mizukami et al, 2014).…”
Section: Discussionmentioning
confidence: 99%